PCI compliance : understand and implement effective PCI data security standard compliance - Chuvakin, Anton (Syngress, 2012)
The credit card industry established the PCI Data Security Standards to provide a minimum standard for how vendors should protect data to ensure it is not stolen by fraudsters. PCI Compliance, 3e, provides the information readers need to understand the current PCI Data Security standards, which have recently been updated to version 2.0, and how to effectively implement security within your company to be compliant with the credit card industry guidelines and protect sensitive and personally identifiable information. Security breaches continue to occur on a regular basis, affecting millions of customers and costing companies millions of dollars in fines and reparations. That doesn't include the effects such security breaches have on the reputation of the companies that suffer attacks. PCI Compliance, 3e, helps readers avoid costly breaches and inefficient compliance initiatives to keep their infrastructure secure. Provides a clear explanation of PCI. Provides practical case studies, fraud studies, and analysis of PCI. The first book to address version 2.0 updates to the PCI DSS, security strategy to keep your infrastructure PCI compliant.